Inter-limb differences in in-vivo tendon behavior, kinematics, kinetics and muscle activation during running - Jacques, T.; Bini, R.; Arndt, A. (Journal of Biomechanics, 2022)
Overloading of tendon tissue may result in overuse tendon injuries in runners. One possible cause of overloading could be the occurrence of biomechanical inter-limb differences during running. However, scarce information exists concerning the simultaneous analysis of inter-limb differences in external and internal loading-related variables in habitual runners. In this study ground reaction force, joint kinematics, triceps surae and tibialis anterior activations, and medial gastrocnemius muscle-tendon junction displacement were assessed bilaterally during treadmill running at 2.7 m.s-1 and 4.2 m.s-1. Statistical parametric t-tests and effect sizes were calculated to identify eventual inter-limb differences across the stance phase and stride cycle. Hip flexion angle was 9° greater (p = 0.03, ES = 0.30) in the non-preferred limb during the flight phase at 4.2 m.s-1. Hip extension velocity was 45 deg.s-1 greater (p = 0.04, ES = 0.41) during ground contact and 25 deg.s-1 greater (p = 0.02, ES = 0.41) immediately after toe-off in the non-preferred limb at 4.2 m.s-1. Hip extension velocity was also 40 deg.s-1 greater (p = 0.01, ES = 0.46) in the non-preferred limb prior to touch-down at 4.2 m.s-1. Brief inter-limb differences in joint kinematics were not accompanied by inter-limb differences in variables associated to internal loading, suggesting they are unlikely to be underlying factors leading to tendon overloading in healthy non-injured runners.